Chirality‐Assisted Ring‐Like Aggregation of Aβ(1–40) at Liquid–Solid Interfaces: A Stereoselective Two‐Step Assembly Process1. Issue 7 (22nd December 2014) - Gao, Guanbin; Zhang, Mingxi; Lu, Pei; Guo, Guanlun; Wang, Dong; Sun, Taolei
Abstract Molecular chirality is introduced at liquid–solid interfaces. A ring‐like aggregation of amyloid Aβ(1–40) on N‐isobutyryl‐L‐cysteine (L‐NIBC)‐modified gold substrate occurs at low Aβ(1–40) concentration, while D‐NIBC modification only results in rod‐like aggregation. Utilizing atomic force microscope controlled tip‐enhanced Raman scattering, we directly observe the secondary structure information for Aβ(1–40) assembly in situ at the nanoscale. D‐ or L‐NIBC on the surface can guide parallel or nonparallel alignment of β‐hairpins through a two‐step process based on electrostatic‐interaction‐enhanced adsorption and subsequent stereoselective recognition. Possible electrostatic interaction sites (R5 and K16) and a chiral recognition site (H14) of Aβ(1–40) are proposed, which may provide insight into the understanding of this effect.